Norma podstawowa w Czystej Teorii Prawa Hansa Kelsena - Huk, Marta Zuzanna (ETHICS IN PROGRESS, 2014)
The aim of following paper is to indicate that the notion of Grundnorm, described by Hans Kelsen in second edition of his Pure Theory of Law (Kelsen, 1960), is in fact a necessity in every construction of normative order – understood as a coercive design. I attempt to prove this point by explaining how Kelsen as the founder of legal normativism is making a clear distinction between effectiveness and validity of basic norm, in context of existing legal order. This leads to me to a conclusion, that as long as we presuppose law as methodologically autonomous concecpt, the Grundnorm must be regarded as its integral conditio sine qua non.